Dynamique des paysages et perspectives de développement durable sur la petite cote et dans le delta du Sine – Saloum (Sénégal) - Gabriela Ackermann; Frédéric Alexandre; Julien Andrieu; Catherine Mering; Claire Ollivier (VertigO)
Scientists have to appropriate the sustainable development concept. Multipartenarial research programs involving southern and northern researchers and institutions are already applying this concept. The authors selected two cases of landscape evolution dealing with coastal resources and geographical uses in the Petite Côte region and in the Sine-Saloum delta (Senegal). The cases studied were built-up growth of the principal city on the region and the mangrove dynamics of the Saloum delta.